AVAILABILITY OF ESSENTIAL MEDICINES IN PUBLIC HEALTH FACILITIES OF JIMMA ZONE, SOUTHWEST ETHIOPIA - Mathewos, Eyassu; Beyene, Waju; Gebissa, Feyera; Ololo, Shimeles; Melese, Dejene; Dagne, Tesfaye; Getachew, Muluneh (Universal Journal of Pharmaceutical Research, 2022)
Background: Availability is the relationship between the type and quantity of product or services needed and the type and quantity of product or services provided. Availability of essential medicines at facility level is an important factor to address patients' satisfaction and increase their health seeking behavior. The objective of this study is to determine the availability and associated factors of essential medicines in public health facilities of Jimma zone, South West Ethiopia. Methods: Facility-based cross-sectional study design was employed. Based on WHO recommendation, thirty health facilities were selected from five districts and six health facilities were chosen from each district of the zone. Availability of 29 key essential medicines that were selected from 2014 Ethiopian national essential medicine list were checked in stores and dispensaries as well as the store keepers, head of health facilities and dispensaries were selected for interview. The data were checked for completeness, edited, and coded then entered and analyzed using excels 2016 and SPSS version 23. Descriptive statistics were computed and tables, graphs and numerical summary presented results. Result: Average availability of selected core essential medicines (n=29) was 78.6% in surveyed health facilities. With regard to stock level, 8% of the surveyed medicines were in critical level, 55.2% were in safe level and 36.8% were in over stock level. Six hundred six patients were participated in the study with a response rate of 97%. Among total respondents, 77.7% left the facility with all of their prescribed medicines while 22.3% received only part of their prescribed medicines. Conclusion: The availability of essential medicines was fairly high in surveyed health facilities during the study period. In this study, many patients seeking treatment in public health facilities failed to obtain significant proportion of prescribed medicines. Peer Review History: Received: 5 October 2021; Revised: 9 November; Accepted: 12 December; Available online: 15 January 2022 Academic Editor: Dr. A.A. Mgbahurike , University of Port Harcourt, Nigeria, amaka_mgbahurike@yahoo.com Reviewers: Dr. A.A. Mgbahurike, University of Port Harcourt, Nigeria, amaka_mgbahurike@yahoo.com Dr. George Zhu, Tehran University of Medical Sciences, Tehran, Iran, sansan4240732@163.com